Expression of Components of the Renin-Angiotensin System in Pyogenic Granuloma - Papali'i-Curtin, Jessica C.; Brasch, Helen D.; van Schaijik, Bede; de Jongh, Jennifer; Marsh, Reginald W.; Tan, Swee T.; Itinteang, Tinte (Frontiers in Surgery, 2019)
Background: There is a growing body of research demonstrating expression of the renin-angiotensin system (RAS) by a putative embryonic stem cell (ESC)-like population within vascular anomalies. This study investigated the expression of components of the RAS in relation to the putative ESC-like population within pyogenic granuloma (PG) that we have recently reported. Methods: PG samples from 14 patients were analyzed for the expression of components of the RAS: pro-renin receptor (PRR), angiotensin converting enzyme (ACE), angiotensin II receptor 1 (ATIIR1) and angiotensin II receptor 2 (ATIIR2), using 3,3-diaminobenzidine (DAB) immunohistochemical (IHC) staining. Immunofluorescence (IF) IHC staining was performed to localize these proteins on four of the PG samples. RT-qPCR was performed on two snap-frozen PG samples. Western blotting (WB) was performed on one snap-frozen PG sample and two PG-derived primary cell lines. Results: DAB IHC staining demonstrated the expression of ACE, PRR, ATIIR1 and ATIIR2 in all 14 PG tissue samples. RT-qPCR analysis confirmed abundant mRNA transcripts for PRR, ACE, AIITR1 and ATIIR2, relative to the housekeeping gene. WB confirmed the presence of PRR, ATIIR1 and ACE in the PG tissue sample, and PRR and ATIIR1, in the PG-derived primary cell lines. IF IHC staining demonstrated the expression of PRR, ACE, ATIIR1 on the primitive population that expressed NANOG, SOX2 on the ERG+ endothelium of the microvessels within PG. Conclusion: We have demonstrated the expression of PRR, ACE and ATIIR1 by the putative the ESC-like population within PG.